Architectural History and Globalized Knowledge: Gottfried Semper in London - Hildebrand, Sonja (2021)
Gottfried Semper's years of exile in London (1850-55) were a time of highly inspiring experiences. The London of the Great Exhibition offered the German architect an immense trove of objects for study and an intellectual environment that provided seminal impulses for his innovative cultural-historical theory of architecture. In this revolutionary period, not only politics and society were in radical upheaval, but also the world of art and science. The internationalization, and indeed globalization, of knowledge was thereby a particularly distinctive phenomenon, the central site of which was the capital of the British Empire. The present volume, resulting from a collaborative SNSF research project of the Institute for the History and Theory of Art and Architecture, Università della Svizzera italiana, and the Institute for the History and Theory of Architecture, ETH Zurich, positions Semper as both an observer and actor in this period. It goes beyond focusing on Semper as an individual person and considers his work as a designer, teacher, and writer of architecture against the backdrop of the historical, architectural, and disciplinary surroundings. The international contributors also address the persistence of Semper's London concepts in his later work, as well as his overarching legacy in the history of ideas.